Promoting Skill-Building Programs for Adolescents and Children with Disabilities - G.A, Akinwale, (Journal of Neonatal Surgery, 2025)
The paper explored the Skill-Building Program for adolescents and children with developmental disabilities, a group facing unique challenges despite the proven benefits of such activities for social, emotional, and academic development. Previous studies have found that these children can be supported with infrastructure, stigma, inadequate training for educators and coaches, and limited adaptive programs. The impact of these barriers on children and adolescents' self-esteem and inclusion, while emphasising the need for supportive environments and policies. Adolescents with disabilities face significant barriers that limit their participation in these activities. This review explores the key challenges that hinder their involvement, including physical inaccessibility, institutional and policy limitations, attitudinal barriers, financial constraints, and psychological factors. Studies indicate that inaccessible facilities, lack of inclusive policies, negative societal perceptions, and high costs contribute to the exclusion of students with disabilities from ECAs. These barriers not only restrict their opportunities for social integration but also impact their overall well-being and skill development. Despite increasing awareness of inclusive education, participation rates for adolescents and children with disabilities remain low. Addressing these barriers requires the implementation of inclusive policies, infrastructure improvements, educator training, and community support programs. Recommendations focus on inclusive legislation, technological solutions, community-based initiatives, and greater advocacy through NGOs and global frameworks like the UN Convention on the Rights of Persons with Disabilities (CRPD). This review underscores the importance of multi-sectoral collaboration to ensure equitable access to enriching extracurricular opportunities for all adolescents and children, regardless of ability. This paper noted the need for further research and policy interventions to ensure equal access to extracurricular activities for all children and adolescents', regardless of ability.